The genealogy of aesthetics - Faas, Ekbert (Cambridge University Press, 2002)
Is it body or spirit that makes us appreciate beauty and create art? The distinguished Canadian critic Ekbert Faas argues that, with occasional exceptions like Montaigne and Mandeville, the mainstream of western thinking about beauty from Plato onwards has greatly overemphasized the spirit. This study redresses this imbalance, and offers a radical re-reading of thinkers like Plato, Augustine, Kant, Hegel, Heidegger and Derrida. Professor Faas attacks both the traditional and postmodern consensus, and offers a new pro-sensualist aesthetics, heavily influenced by Nietzsche, that draws on contemporary cognitive science